Associação dos achados de neuroimagem estrutural e funcional e os polimorfismos genéticos em transtornos do humor: revisões sistemáticas e meta-análise - Pereira, Licia Pacheco (2017)
Genetic-neuroimaging paradigms could provide insights regarding the pathophysiology of bipolar disorder (BD) and major depression disease (MDD). Nevertheless, findings have been inconsistent across studies. Two systematic reviews (SR) of gene-imaging studies involving individuals with BD and MDD were conducted across electronic major databases from inception until January 9th, 2017 (BD) and June 30th (MDD). We performed meta-analyses (MA) of all available studies reporting replicated findings (at least 3 studies using the same methodology and genetic polymorphism). Forty-four studies met eligibility criteria for BD SR (N=2,122 BD participants) and 65 studies for the MDD SR (N=5,094 MDD participants). In the BD SR, 26 gene variants were investigated across candidate gene studies and 4 studies used a genome-wide association approach. Replicated evidence (i.e. in >2 studies) suggests that individuals with BD carrying the BDNF Val66Met risk allele could have reduced hippocampal volumes compared to non-carriers. The MDD SR provided sufficient data to perform MAs. The magnitude and direction of the genetic-imaging relationship were estimated and potential influence of demographic, clinical and methodological characteristics of studies were assessed for region of interest (ROI) metrics. Whole-brain structural and functional results were included in Seed-based d Mapping (SDM) software. No significant difference in total hippocampal volume was detected in carriers of the risk-allele in compared to homozygous for the wild allele for both 5-HTTLPR and BDNF polymorphisms in MDD or healthy controls (HC). Possible sources of heterogeneity (I2 = 16.5 to 76.4 depending on the MA) were explored (e.g. age, gender, medication status). Significant decreases of fractional anisotropy (FA) in several white matter tracts were observed in association with 5-HTTLPR polymorphism and MDD. Moreover, conjoint structural and functional differences were detected the right middle frontal cortex in MDD patients carriers of the BDNF polymorphism risk allele compared to MDD non-carriers. The BD SR underscores the potential of gene-neuroimaging paradigms to provide mechanistic insights for BD. Suggestions to improve the reproducibility of this emerging field are provided, including the adoption of a trans-diagnostic approach. Our results of MDD SR and MA further characterize imaging-genetic associations in MDD. Future studies are warranted to further elucidate sources of heterogeneity. Keywords: Bipolar disorder; Major depression; Genetic polymorphisms; Neuroimaging; Magnetic resonance imaging; MRI; Functional MRI; FMRI; Diffusion tensor imaging; DTI; Voxel-based morphometry; VBM; Morphometry; 5-HTTLPR; BDNF; COMT; Meta-analysis